Composition of Types and Abundance of Perifitons in Coban Talun Hulu River Brantas, Batu City -East Java - Luthfiana, Mauludiya; Latuconsina, Husain; Zayadi, Hasan (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic), 2024)
This research was conducted at Coban Talun Hulu Sungai Brantas, Batu City, East Java in August 2020, this study aims to inventory, analyze the abundance of periphyton, analyze water parameters in the Brantas Coban Talun Hulu River. Determination of the location for sampling purposive. Physical and chemical parameters measured include temperature, pH, DO, turbidity and salinity. This study found 17 periphytic families, consisting of Naviculaceae, Melosiraceae, Bacillariaceae, Skeletonemaceae, Rhizosoleniaceae, Coscinodiscaceae, Peridiniaceae, Gonyaulacaceae, Triceratiaceae, Protoperidiniaceae, Striatellaceae, Dinophysaceae, Lithodesmiaceae, Leptocylindraceae, and Striatellaceae. The results of the abundance of periphyton showed that Coban Talun was at a good level. Periphyton community which is dominated by Bacillariophyceae group shows good water quality. Based on the analysis of water quality parameters, Coban Talun is in the good category. Although high anthropogenic and tourism activities are presented at Coban Talun, some riparian vegetation can reduce water pollution and stabilize dissolved and suspended soils caused by human activities. It can be concluded that Coban Talun is capable of supporting periphytonic life as well as